Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Challenges associated with metal chelation therapy in alzheimer's disease - Hegde, Muralidhar L.; Bharathi, P.; Suram, Anitha; Venugopal, Chitra; Jagannathan, Ramya; Poddar, Pankaj; Srinivas, Pullabhatla; Sambamurti, Kumar; Rao, Kosagisharaf Jagannatha; Scancar, Janez; Messori, Luigi; Zecca, Luigi; et al. (Journal of Alzheimers Disease, 2009)
A close association between brain metal dishomeostasis and the onset and/or progression of Alzheimer's disease ( AD) has been clearly established in a number of studies, although the underlying biochemical mechanisms remain obscure. This observation renders chelation therapy an attractive pharmacological option for the treatment of this disease. However, a number of requirements must be fulfilled in order to adapt chelation therapy to AD so that the term ``metal targeted strategies'' seems now more appropriate. Indeed, brain metal redistribution rather than brain metal scavenging and removal is the major goal of this type of intervention. The most recent developments in metal targeted strategies for AD will be discussed using, as useful examples, clioquinol, curcumin, and epigallocatechin, and the future perspectives will also be outlined.
Keywords: Alzheimer's disease; clioquinol; cuprizone; metal dishomeostasis; metal ions; nanomedicine; Parkinson's disease; polyphenols

Colossal increase in negative magnetization, exchange bias and coercivity in samarium chromite due to a strong coupling between Sm3+-Cr3+ spins sublattices - Gupta, Preeti; Bhargava, Richa; Poddar, Pankaj (Journal of Physics D-Applied Physics, 2015)
We report giant temperature dependent negative magnetization (magnetization reversal) along with a large exchange bias and large coercivity in SmCrO3. The static magnetization measurements show the negative magnetization below similar to 192 K, due to competition between the external field, thermal activation energy and antiparallel Sm3+-Cr3+ spin interaction. At further lower temperatures, Sm3+ spins show an increased alignment due to the internal induced field of Cr3+ spins with minimum magnetization similar to - 0.037 emu g(-1). The temperature dependent exchange bias shows non-monotonic behavior. At 35 K, the exchange bias ceases to exist due to the orientation of Sm3+ moments with respect to canted Cr3+ moments. The crossover temperature decreases from similar to 191 K at 100 Oe to similar to 153 K at 250 Oe. The training effect further confirms the exchange bias in SmCrO3. The dynamic magnetization measurements exhibit anomalies around spin reorientation transition (T-SR similar to 34 K) and Neel transition (T-N similar to 192 K) which is consistent with static measurement and no frequency dependence was observed. The room temperature Raman spectra of SmCrO3 show peaks at similar to 364, similar to 375 and similar to 456 cm(-1) suggesting O-Cr-O bending modes within the octahedral.
Keywords: exchange bias; multiferroics etc; negative magnetization; samarium chromite; spin reorientation

Construction of polynuclear lanthanide (Ln = Dy-III, Tb-III, and Nd-III) cage complexes using pyridine-pyrazole-based ligands: versatile molecular topologies and smm behavior - Bala, Sukhen; Sen Bishwas, Mousumi; Pramanik, Bhaskar; Khanra, Sumit; Fromrn, Katharina M.; Poddar, Pankaj; Mondal, Raju (Inorganic Chemistry, 2015)
Employment of two different pyridyl pyrazolyl-based ligands afforded three octanudear lanthanide(III) (Ln = Dy, Tb) cage compounds and one hexanudear neodymium(III) coordination cage, exhibiting versatile molecular architectures including a butterfly core. Relatively less common semirigid pyridyl pyrazolyl-based asymmetric ligand systems show an interesting trend of forming polynuclear lanthanide cage complexes with different coordination environments around the metal centers. It is noteworthy here that construction of lanthanide complex itself is a challenging task in a ligand system as soft N-donor rich as pyridyl pyrazol. We report herein some lanthanide complexes using ligand containing only one or two O-donors compare to five N-coordinating sites. The resultant multinuclear lanthanide complexes show interesting magnetic and spectroscopic features originating from different spatial arrangements of the metal ions. Alternating current (ac) susceptibility measurements of the two dysprosium complexes display frequency- and temperature-dependent out-of-phase signals in zero and 0.5 T direct current field, a typical characteristic feature of single-molecule magnet (SMM) behavior, indicating different energy reversal barriers due to different molecular topologies. Another aspect of this work is the occurrence of the not-so-common SMM behavior of the terbium complex, further confirmed by ac susceptibility measurement.